Well-designed : how to use empathy to create products people love - Kolko, Jon (Boston, Massachusetts : Harvard Business Review Press, 2014)
"A new way to create-and then disrupt Industry disruption is no longer isolated to a unique product or service. Today's consumer needs engagement in order to be swayed to interact, connect, and buy your next offering. Achieve this and you'll achieve success. Sharp and refreshing, design insider and expert Jon Kolko offers a new view and usable process for conceiving and building powerful, emotionally resonant new products in this new book. In Well-Designed, Kolko-VP at MyEdu and Founder and Director of the Austin Center for Design--shows how deep, meaningful engagement happens when products and services are delivered in an authentic way, when consumers see them less like manufactured artifacts and more like good friends. The key is empathy-driven design thinking, using a process of storytelling and iteration, with results that provoke emotion, change behavior, and create deep engagement. Kolko, who has been engaged in this process of design for more than 15 years, now shares a concrete set of steps for identifying lucrative opportunities, designing for innovation, and producing products that have deep, meaningful emotional engagement. By following this process, readers will learn how to raise the role of design to a strategic competency"--
By design -- Product-market fit: finding broad appeal -- Behavioral insights: identifying latent needs and desires -- Product strategy: sketching a playbook of emotional value -- Product vision: crafting the product details -- Shipping
Includes bibliographical references and index
Keywords: Product design; New products; Consumer behavior; Marketing research